Sustainable building conservation : theory and practice of responsive design in the heritage environment - Prizeman, Oriel (RIBA Publishing, 2015)
"Principles of conservation and sustainability are easily married but often at odds for architects under increasing pressure to navigate the energy needs of older buildings. By incorporating UK and international case studies together with more theoretical essays the book seeks to identify overlaps in the interests of energy and building conservation. The varied expertise of the contributors--architects, surveyors, consultants and academics--demonstrates the use of qualitative and quantitative frames of reference. The second part of the book showcases sustainable domestic and non-domestic heritage projects, translating the challenges of the preceding research into varied methods that practitioners can use to question and review their everyday work."--Page 4 of cover